Analyzing ACEI-Furosemide and ARB-Furosemide Drugs Combination on Hypertension and Chronic Kidney Disease Patients - Hesti Effendi; Helmi Arifin; Nasrul Zubir (International Journal Labs, 2023)
The purpose of this study was to compare the efficacy of ACE-inhibitor + Furosemide and ARB + Furosemide in lowering creatinine, urea, and blood pressure in individuals with hypertension and chronic renal disease. This is a retrospective study in which data were extracted from the medical records of patients with hypertension and chronic kidney disease in the Internal Medicine Ward of the General Hospital dr. M. Jamil Padang in West Sumatera. A 2-by-3 ANOVA hypothesis test design was utilized. The hypothesis was evaluated using an alpha value of 0.05. The results demonstrated that the ARB + Furosemide combination was superior to the ACE-Inhibitor + Furosemide combination by 86.2%. In addition, this study demonstrated that the medication combinations ACE inhibitor plus furosemide and ARB plus furosemide were equally efficient in lowering creatinine, urea, and blood pressure in individuals with hypertension and chronic renal disease. The researchers found that antihypertensive medicines, including the ACE-Inhibitor + Furosemide combination and the ARB + Furosemide combination, can be administered at levels determined by the patient's clinical situation. Also, while selecting a pharmacological combination between an ACE inhibitor and furosemide or an ARB and furosemide, it is important to consider the adverse effects of the drugs. For instance, it is preferable to combine ARB with Furosemide.